Qualidade da madeira de árvores de guapuruvu (schizolobium parahyba (vell.) blake) com 15 anos provenientes de área de recuperação florestal - Athanázio-Heliodoro, Julia Carolina [UNESP] (2015)
Guapuruvu (Schizolobium parahyba (Vell) Blake) is a native species of Atlantic Forest that has rapid development and large gain in volume. Some pioneers studies about the technological potential of guapuruvu's wood highlighting the exuberant growth of the species and pointing out some possibilities of industrial use, missing for that a study about the physical and mechanical properties and the quality of its wood. Qualified as a pioneer species in forest succession, has been used in forest recovery áreas where a conditioning aspect is the selection of species that perform well their environmental paper and also generate a financial return to the forest owner by a possible commercial use during the second phase of the forest succession, when these species can be withdrawn through forest. This study aimed to define the technological potential of wood guapuruvu (S. parahyba), obtained from forest recovery areas of the Atlantic Forest in the region of Botucatu-SP city by evaluating the physical and mechanical properties and the wood quality of these trees starting by radial variation of these properties and specific gravity - obtained by X-ray attenuation - characterization of different types of wood. Under these conditions, the wood has compressive strength parallel to the fibers of 21.47MPa, being positioned in the C20 - eudicotyledonous strength class of NBR7190. Specific gravity was 336 kg/m³ and basic density it was 290 kg/m³. In all tests, the species had medium coefficients of variation without difference-statistic between the sides of the wood, despite the presence of reaction wood, showing the homogeneity of this wood. Demonstrated potential for use in categories as lightweight construction, temporary use and offset plates.